The Validity of Public Opinion Research on Future Technologies - Grzegorczyk , Tomasz (Studia Oeconomica Posnaniensia, 2017)
More and more public opinion research is being conducted on future technologies and their multidimensional effects. The main aim of this paper is to answer the question: what is the validity of such research from a theoretical and practical point of view? Furthermore, the paper addresses the limitations associated with the orientation of such research for the future, as well as the interaction between society and technology. The main conclusion of this paper is that public opinion research on future technologies fulfis the main objectives of sociology as a science by replying to the following questions: what will future society look like and how to indicate its proper direction. However, public opinion research is not sufficient. It is recommended to make use of other social sciences oriented to the future. We appeal for further sociological research on emerging technology and society, before the "black box" becomes closed.